2014
DOI: 10.22146/ijc.21252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pb(II) Imprinted Carboxymethyl Chitosan and the Application as Sorbent for Pb(II) Ion

Abstract: The aims of this research is to synthesize Pb(II) imprinted polymers with carboxymethyl chitosan (CMC) as polymers and bisphenol A diglycidyl ether (BADGE) as cross-linker (Pb-IIP). Chitosan (CTS), non imprinted polymer (NIP) and NIP gave higher adsorption selectivity for Pb(II)/Ni(II) and Pb(II)/Cu(II), whereas Pb-IIP showed higher adsorption selectivity for Pb(II)/Cd(II).The hydrogen bonding dominated interaction between Pb(II) ion on NIP and Pb-IIP. Keywords: ion imprinted polymers; carboxymethyl chitosan; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Figure 8 illustrates the synthesis scheme of the NM/CMKCNi(II)IIP adsorbent through several steps. CMKC, which has bound Ni(II), was crosslinked with BADGE, this binding model has been proposed by previous researchers, who conducted cross-linking experiments of carboxymethyl cellulose polymers with BADGE [26]. The CMKC crosslinking reaction in this study proceeded as the reaction is shown in Figure 9.…”
Section: Synthesis and Characterization Of Nm/cmkcni(ii)iipmentioning
confidence: 57%
See 1 more Smart Citation
“…Figure 8 illustrates the synthesis scheme of the NM/CMKCNi(II)IIP adsorbent through several steps. CMKC, which has bound Ni(II), was crosslinked with BADGE, this binding model has been proposed by previous researchers, who conducted cross-linking experiments of carboxymethyl cellulose polymers with BADGE [26]. The CMKC crosslinking reaction in this study proceeded as the reaction is shown in Figure 9.…”
Section: Synthesis and Characterization Of Nm/cmkcni(ii)iipmentioning
confidence: 57%
“…The printed polymer technique produces polymers with specific templates, which are recognized by the ion/similar molecules contacted after ion imprinting [25]. [26] carried out cross-linking of carboxymethyl chitosan with bisphenol A diglycidyl ether (BADGE); this cross-linking brought the carboxymethyl chitosan carbonyl groups closer together which allowed the carbonyl lone pair to form a covalent bond to bind to the Pb(II) metal ion. The binding of metal ions is followed by the release of Pb(II) ions which are bound to the polymer, resulting in the formation of gaps printed by Pb(II) ions, on polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Even at the low concentration, Pb(II) pollution could damage the central nervous system and cause mortality [8]. Therefore, Pb(II) removal process has gained the highest interest over the past several years [9][10][11][12][13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Penggantian kumpulan karboksimetil yang dilakukan menggunakan kaedah pengalkilan secara terus terhadap rantai kitosan. Penambahan kumpulan karboksimetil dilakukan bukan sahaja akan meningkatkan bilangan oksigen pada rantai polimer, ia juga untuk mengurangkan fasa kehabluran di dalam rantai polimer induk (Masykur et al 2014).…”
unclassified